2018
DOI: 10.1002/pc.25032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of functionalized molybdenum disulfide (MoS2) with triazine derivatives on the thermal stability and flame retardancy of intumescent Poly(lactic acid) system

Abstract: Molybdenum disulfide (MoS 2 ) with two-dimensional (2D) lamellar structure was functionalized with melamine-cyanuric acid (MCA) hybrids via a facile way. A core-shell composite particle (MoMA) was obtained. Acting as one kind of synergistic flame retardant, it was mixed with traditional intumescent flame retardant (IFR) to prepare the flame retardant poly(lactic acid) composites by melt blending. UL-94 V-0 rating and LOI value of 29.8% for PLA composites were achieved while the total amount of flame retardants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…6. The fracture surface of VER is smooth indicating brittle failure happened in bending tests 29 . However, ductile fracture was found for the VER/PEPABFR and VER/DOPOBFR systems.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…6. The fracture surface of VER is smooth indicating brittle failure happened in bending tests 29 . However, ductile fracture was found for the VER/PEPABFR and VER/DOPOBFR systems.…”
Section: Resultsmentioning
confidence: 97%
“…The fracture surface of VER is smooth indicating brittle failure happened in bending tests. 29 However, ductile fracture was found for the VER/PEPABFR and VER/DOPOBFR systems. The fracture surfaces are rough and irregular suggesting a stronger force between flame retardant and resin.…”
Section: Mechanical Performance Of Ver Systemsmentioning
confidence: 96%
“…In recent years, the improvement of flame retardancy without sacrificing the mechanical properties of PLA has been studied extensively by researchers 15,18–23 . Below is a summary of three major ways of enhancing mechanical properties of flame‐retardant PLA: Toughening agentsAdding the toughening agents, such as thermoplastic polyurethane elastomer (TPU), 24 polyethylene glycol (PEG), 25 castable polyurethane elastomer (CPU), 26 PA‐HDA (synthesized from phytic acid and 1,6‐hexanediamine), crosslinking polyurethane (CPU) 27 and plasticizer‐poly(propylene glycol) 28 to improve the mechanical property of PLA are the most common methods. Song 29 and Yang 30 used the biodegradable material polyethylene glycol (PEG) as the plasticizer to improve the mechanical properties of PLA composites.…”
Section: Introductionmentioning
confidence: 99%
“…Tawaih et al reported that the peak heat release rate (pHRR) and total heat release (THR) of PLA composites could be reduced by 76.5% and 76.9%, respectively, with 2 wt% of sodium metaborate intercalated azo‐boron/reduced graphene oxide hybrids . Xu et al functionalized molybdenum disulfide with melamine‐cyanuric acid (MoS 2 @MCA) . The results revealed that the limited oxygen index (LOI) of the PLA composites could increase up to 29.8% and rate V‐0 level in UL‐94 test with 3 wt% MoS 2 @MCA and 9 wt% traditional intumescent flame retardant.…”
Section: Introductionmentioning
confidence: 99%